Likelihood of post-COVID condition in people with hybrid immunity: data from the German National Cohort (NAKO) - Mikolajczyk, Rafael; Diexer, Sophie; Klee, Bianca; Pfrommer, Laura; Purschke, Oliver; Fricke, Julia; Ahnert, Peter; Gabrysch, Sabine; Gottschick, Cornelia; Bohn, Barbara; Brenner, Hermann; Buck, Christoph; et al. (Journal of infection, 2024)
Objectives - The risk of Post-COVID-19 condition (PCC) under hybrid immunity remains unclear. - Methods - Using data from the German National Cohort (NAKO Gesundheitsstudie), we investigated risk factors for self-reported post-infection symptoms (any PCC is defined as having at least one symptom, and high symptom burden PCC as having nine or more symptoms). - Results - Sixty percent of 109,707 participants reported at least one previous SARS-CoV-2 infection; 35% reported having had any symptoms 4-12 months after infection; among them 23% reported nine or more symptoms. Individuals, who did not develop PCC after their first infection, had a strongly reduced risk for PCC after their second infection (50%) and a temporary risk reduction, which waned over 9 months after the preceding infection. The risk of developing PCC strongly depended on the virus variant. Within variants, there was no effect of the number of preceding vaccinations, apart from a strong protection by the fourth vaccination compared to three vaccinations for the Omicron variant (odds ratio = 0.52; 95% confidence interval 0.45-0.61). - Conclusions - Previous infections without PCC and a fourth vaccination were associated with a lower risk of PCC after a new infection, indicating diminished risk under hybrid immunity. The two components of risk reduction after a preceding infection suggest different immunological mechanisms.